Severe mortality impact of the 1957 influenza pandemic in Chile. Issue 3 (31st March 2017) - Chowell, Gerardo; Simonsen, Lone; Fuentes, Rodrigo; Flores, Jose; Miller, Mark A.; Viboud, Cécile
Abstract : Introduction: Epidemiological studies of the 1957 influenza pandemic are scarce, particularly from lower‐income settings. Methods: We analyzed the spatial–temporal mortality patterns of the 1957 influenza pandemic in Chile, including detailed age‐specific mortality data from a large city, and investigated risk factors for severe mortality impact across regions. Results: Chile exhibited two waves of excess mortality in winter 1957 and 1959 with a cumulative excess mortality rate of 12 per 10 000, and a ~10‐fold mortality difference across provinces. High excess mortality rates were associated with high baseline mortality ( R 2 =41.8%; P =.02), but not with latitude ( P >.7). Excess mortality rates increased sharply with age. Transmissibility declined from R =1.4‐2.1 to R =1.2‐1.4 between the two pandemic waves. Conclusions: The estimated A/H2N2 mortality burden in Chile is the highest on record for this pandemic—about three to five times as severe as that experienced in wealthier nations. The global impact of this pandemic may be substantially underestimated from previous studies based on high‐income countries.